Strategi Pembelajaran Diferensiasi untuk Mengakomodasi Keragaman Gaya Belajar Siswa - Rahma, Maulidatul; Damayanti, Ayu Maya; Widyanto, Nur; Febriansyah, Galang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the differentiated learning strategies teachers implement to accommodate diverse student learning styles (visual, auditory, and kinesthetic) and to examine their contributions to student engagement and understanding. The study used a descriptive qualitative approach, mapping learning needs at the beginning of the lesson using questionnaires, interviews, and classroom observations as the basis for planning differentiation in content, process, and product. Results show that teachers facilitated visual learners with images, diagrams, and concept maps; auditory learners through discussions and reading aloud; and kinesthetic learners through demonstrations and hands-on practice. In conclusion, implementing this data-based differentiation was associated with increased learning comfort, motivation, participation, and a more inclusive learning environment. Keywords: Content-Process-Product Differentiation, Learning Styles (VAK), Learning Engagement, Differentiated Learning, Inclusive Learning